Elaboration of Libertarianism takes the view of humanity in the dual profession law - Gregorius Yoga Panji Asmara; Yovita Arie Mangesti (Universitas Katolik Soegijapranata Semarang, 2020)
The advancement of civilization has led to the creation of a dual form of the doctor-advocate profession which is confronted with many conflicts of interest between two opposing interests between doctors who are also advocates. This paper uses a legal, conceptual, and eclectic approach to positive law in the dual profession of doctor-advocate with humanitarian paradigm libertarianism. The results of this study resulted in the construction of the dual law of the doctor-advocate profession, providing an understanding that each individual has the right to decide on goals to be achieved based on morality and sensitivity to fair and civilized human values, so that in constructing the dual law of the doctor-advocate profession it is done only to defend the weak, without having to leave the identity and independence of the profession as doctors and advocates.